Esophagogastric complications in radiofrequency and cryoballoon catheter ablation of atrial fibrillation. (10th May 2022) - Oikawa, Jun; Fukaya, Hidehira; Wada, Takuya; Kishihara, Jun; Sato, Tetsuro; Matsuura, Gen; Nakamura, Hironori; Ishizue, Naruya; Katada, Chikatoshi; Tanabe, Satoshi; Niwano, Shinichi; kusano, Chika; et al.
Abstract: Introduction: Direct comparison studies about the incidence of esophagogastric complications between radiofrequency (RF) and cryoballoon (CB) catheter ablation (CA) for atrial fibrillation (AF) have been scarce. We sought to elucidate the relationship between the pulmonary vein isolation (PVI) modalities and esophagogastric complications. Methods: The study population consisted of 254 patients who underwent CA for AF from November 2017 to October 2018. Finally, 160 patients were enrolled and divided into the RF and CB groups. Esophageal ulcers, gastric hypomotility, and exfoliative esophagitis detected by esophagogastroduodenoscopy were defined as esophagogastric complications in this study. Results: The median age was 68 years old, with 34% being females. Esophagogastric complications were observed in 42.5% of patients who underwent CA. According to the detailed esophagogastric complications, the RF group had a higher prevalence of esophageal ulcers than the CB group (19% vs. 0%, p < .0001). There was no significant difference between the two groups regarding gastric hypomotility and exfoliative esophagitis (18% vs. 28%; p = .15 and 16% vs. 21%; p = .42, respectively). Conclusion: Asymptomatic esophagogastric complications were common in CA for AF. The incidence of esophageal ulcers was higher in the RF group than in the CB group, whereas the other esophagogastric complications did not significantly differ.